Study on physical fitness factors affecting race-class of Korea racing cyclists - Park, J.-H.; Seo, T.-B. (Journal of Exercise Rehabilitation, 2020)
The purpose of this study is to compare and analyze the difference of isokinetic muscle functions, anaerobic capabilities, pedaling power and maximum strength according to race-class of Korea racing cyclists. The participants in this study were 57 racing cyclist candidates who graduated from the Korea racing school. One year after graduation, we confirmed race-class of candidates and they were divided into three groups: the first-class racer group (FC, n=14), second-class racer group (SC, n=29), third-class racer group (TC, n=14). The isokinetic muscle strength of trunk and knee flexion/extension was measured using HUMAC NORM and basic physical strength such as squat and bench press was analyzed by Ariel device. As results of this study, % Fat (percentage of body fat) in FC group was the lowest compared to other groups. Isokinetic knee flexion strength was higher in FC group than SC and TC racer groups. Peak and average pedaling power as well as maximum muscle strength were significantly higher in FC group than in other groups. Our findings suggest new evidence that pedaling power and isokinetic muscle strength might be closely associated with race-class of Korea racing cyclists.